Accuracy of community pharmacy blood pressure measurement: a cross-sectional study - Alogaili, Methaq H.; Hussain, Nibras A.; Alsallami, Afnan A.; Fadhil, Musatafa S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Recently, community pharmacy blood pressure measurement has gained popularity as it is easily accessible and cost-effective out-of-office method especially for blood pressure monitoring. However, it’s practical applicability and clinical value has not been fully studied. This study aimed to evaluate the accuracy of community pharmacy blood pressure measurement. Methods: Study participants were adults (390) who measured their blood pressure at different community pharmacies and came to the emergency departments (for confirmation of their blood pressure reading on the same day) of eight major hospitals in Baghdad, Iraq 2024. Participants were directly interviewed and blood pressure measured according to guidelines. Results: The mean age was (44.8±14.2) years of whom (58.7%) were males. The sensitivity was (85.1%), specificity (9.1%), positive and negative predictive values (22.9%, 65.9%), respectively. Paired t test showed significant difference between both systolic and diastolic blood pressure measurements in pharmacies (156.4±21.7 and 91.9±14.2, respectively) and hospital (122.7±15.4 and 77.4±9.50, respectively) (p<0.001). Pearson’s correlation test showed that there was mild positive correlation between measurements in hospital with body mass index (BMI) (r=0.20, p=0.005 and r=0.22, p<0.005, respectively). Conclusions: Community pharmacy blood pressure measurement lack accuracy. Further detailed studies are needed.